2012
DOI: 10.1002/ptr.4602
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Pycnogenol in a Rat Model of Non‐alcoholic Steatohepatitis

Abstract: Oxidative stress is considered as a mechanism of hepatocellular injury in non-alcoholic steatohepatitis (NASH). Pycnogenol (PYC) is the natural plant extract from the bark of Pinus pinaster Aiton. and has potent antioxidant activities. We studied the protective effect of PYC on excessive fat accumulation in the liver fed a methionine-choline deficient (MCD) high-fat diet for 6 weeks. Pycnogenol (10 mg/kg body weight) was orally administered for 5 weeks. At the end of the experiment, blood and liver samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…In this study, we evaluated the effects of PYC on hepatic steatosis and further explored the underlying mechanism in ApoE-deficient mice. Previous studies have shown that PYC effects the regulation of lipid metabolism and possesses protective effects on nonalcoholic steatohepatitis (5,18,38). In line with previous results, we found that PYC reduced body weight gain and decreased plasma lipid and hepatic lipid accumulation in ApoE-deficient mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we evaluated the effects of PYC on hepatic steatosis and further explored the underlying mechanism in ApoE-deficient mice. Previous studies have shown that PYC effects the regulation of lipid metabolism and possesses protective effects on nonalcoholic steatohepatitis (5,18,38). In line with previous results, we found that PYC reduced body weight gain and decreased plasma lipid and hepatic lipid accumulation in ApoE-deficient mice.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, an openlabel controlled study has shown that the supplementation of PYC in 130 subjects with symptoms of metabolic syndrome decreases waist circumference and TG levels and increases HDL levels (5). It has been reported that PYC is involved in lipid metabolism and has a protective capacity against hepatotoxicity and oxidative stress in the livers of mice (18,38,44). The phenols and polyphenols, as the main ingredient of PYC, have been shown to improve hepatic steatosis, including apple polyphenols, resveratrol, polyphenol-rich grape skin extract, and others (3,28,42,54,56).…”
Section: Introductionmentioning
confidence: 99%
“…However, the PYC-treated animals exerted a marked decreased in histological collagen deposition and collagen I expression in comparison to CS and LPS-exposed animals. It has been demonstrated that PYC significantly suppresses fat accumulation and fibrosis in the liver of high-fat diet model and prevents the development of viral myocarditis by decreasing inflammation and fibrosis [910]. These findings indicate that PYC may suppress the fibrotic change in the lung tissue caused by CS and LPS exposure.…”
Section: Discussionmentioning
confidence: 91%
“…Pycnogenol® (PYC, pine bark extract) is a trade name and a standardized mixture of the bark of French maritime pine [8]. Recent reports have demonstrated that PYC significantly suppresses inflammation, fat accumulation, and fibrosis in the liver and heart [910]. In addition, the preventive effect of PYC against wrinkle formation through TGF and type I procollagen has been described [11].…”
mentioning
confidence: 99%
“…The other major important sources of pycnogenol are peanut skin, grape seed, and witch hazel bark. It has been showing highly protective properties against several diseases such as cardiovascular dysfunctions [15], kidney diseases [16], hepatic dysfunctions [17], neuro cognitive disorders [18], diabetes [19], reproductive dysfunctions and infertility [20], skin diseases [21], cancer [22], digestion [23], retinal diseases [24] and other dysfunctions. In fact, beneficial effects of pycnogenol have been showing all over the biological system on both animals and human studies.…”
Section: Introductionmentioning
confidence: 99%